Different Doses of Lumbar Epidural Methylprednisolone Injection and their effect on Pain Control and Blood Glucose Level in Diabetic patients - Fahad Mahmood, Mohammad Mustajab Akhtar, Asad Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Frequency of diabetes mellitus is high between people suffering from lumbar spinal degenerative sickness Despite the fact that injection of steroid in epidural space are recognised to rise the glycaemic Blood amount postoperatively, therefore it is inquiry that decrease dose of methylprednisolone (40mg) cannot rise blood glycaemic level as compare to higher dose of methylprednisolone (80mg) and their effect on pain management of patients. Aim: To evaluate 2 common doses (80mg & 40mg) of methylprednisolone effects which is given through Epidural lumbar route, on glycaemic Blood level and pain management of diabetes mellitus patients to determine an adequate epidural steroid dose. Methods: This was an observational prospective study was conduct at Department of Anaesthesia Hayatabad Medical Complex Peshawar in June 2022. Overall 110 Diabetes mellitus patients were participated. They acquired lumbar epidural, methylprednisolone for spinal stenosis radiculopathy or failed back surgery syndrome. Methylprednisolone dose were given to patients, either 80mg (Group A) or 40 mg (Group B) was determined clinically after the procedure type. Results: HbA1c level was noted in group A 6.21mmol/L while in group B 6.52 mmol/L (p =0.991). The increase in fasting blood glucose (FBG) were greater significantly A Group than in B Group on post procedure day (PPD)1,2&3 (PPD1: 179 mg/dL A Group Vs 146mg/dL in B Group ), (PPD2: 221 mg/dL in A Group Vs 152mg/dL in B Group ) & (PPD3: 202mg/dL in A Group Vs 175mg/dL in B Group ). Fasting blood glucose incidence was >180mg/dL were greater in A Group than in B Group on post procedure day 1&2 (PPD1: A Group=11 vs B Group=5) and (PPD2: A Group=13 Vs B Group= 4). Conclusion: Methylprednisolone increase dose 80mg rise FBG and PDG greater than a decrease dose 40mg with no effect on pain management, employment status, or clinical outcome. Thus, it is recommended that methylprednisolone 40mg will b given rather than 80mg in diabetes mellitus patients with respect to pain management and blood glycaemic level Keywords: Epidural methylprednisolone, back pain, blood glucose.